Network Model With Reduced Metabolic Rate Predicts Spatial Synchrony of Neuronal Activity - Joo, Pangyu; Lee, Heonsoo; Wang, Shiyong; Kim, Seunghwan; Hudetz, Anthony G. (Frontiers in Computational Neuroscience, 2021)
In a cerebral hypometabolic state, cortical neurons exhibit slow synchronous oscillatory activity with sparse firing. How such synchronization spatially organizes as cerebral metabolic rate decreases has not been systemically investigated. We developed a network model of leaky integrate-and-fire neurons with additional dependency on adenosine triphosphate (ATP) dynamics. Neurons were scattered in 2D space and their population activity patterns at varying ATP levels were simulated. The model predicted a decrease in firing activity as the ATP production rate was lowered. Under the hypometabolic condition, oscillatory firing pattern, that is, ON-OFF cycle, arose through a failure of sustainable firing due to the reduced excitatory positive feedback and the rebound firing after slow recovery of ATP concentration. Firing rate oscillation of distant neurons developed at first asynchronously that changed into burst suppression and global synchronization as ATP production further decreased. These changes resembled experimental data obtained from anesthetized rats, as an example of metabolically suppressed brain. Together, this study substantiates a novel biophysical mechanism of neuronal network synchronization under limited energy supply.